Exploring the Antioxidant Activity and Impact on Gut Microbiota of Brassica rapa L. Polysaccharides Based on an in Vitro Digestion and Fermentation Model - Mengying ZHANG; Kaiyue BI; Yuhan WU; Wei LI; Wei LI; Yanbo LI; Yu ZHAO; Wei WANG (Shipin gongye ke-ji)
Objective: This study aimed to investigate the changes in antioxidant activity of turnip polysaccharides during in vitro simulated gastrointestinal digestion and to analyze their effects on gut microbiota diversity using an in vitro fecal anaerobic fermentation model. Methods: The DPPH·, ABTS+· and ·OH scavenging activities of digestion fluids after simulated digestion of turnip polysaccharides were measured. High-throughput 16S rDNA sequencing was used to examine the effects of different concentrations of turnip polysaccharides on the gut microbiota. Results: During simulated gastric digestion, the scavenging activities for DPPH·, ABTS+· and ·OH reached their peak at 1 hour, with values of 33.76%±0.53%, 34.95%±0.35%, and 21.98%±0.45%, respectively. During simulated intestinal digestion, the scavenging rates for DPPH·, ABTS+· and ·OH showed an initial increase followed by a decrease. Gut microbiota analysis revealed that, compared to the initial fermentation stage (CK0), the relative abundance of Firmicutes decreased, while the relative abundance of Bacteroidota increased to varying degrees. The relative abundances of Bifidobacterium, Megasphaera, Parasutterella, Ligilactobacillus, and Faecalibacterium were significantly increased after fermentation compared to the unfermented state (P<0.05). Conclusion: This study demonstrates that turnip polysaccharides can enhance free radical scavenging activity and antioxidant capacity during in vitro simulated digestion. Furthermore, they can modulate the composition and abundance of gut microbiota after in vitro fermentation. The findings provide theoretical insights for the advanced processing of turnip and its potential role in regulating gut microbiota.